2020
DOI: 10.3390/agronomy10010107
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of NH3 Concentrations in Weaner Pig Buildings Based on Setpoint Temperature

Abstract: Ammonia (NH3) concentration has seldom been used for environmental control of weaner buildings despite its impact on environment, animal welfare, and workers’ health. This paper aims to determine the effects of setpoint temperature (ST) on the daily evolution of NH3 concentration in the animal-occupied zone. An experimental test was conducted on a conventional farm, with ST between 23 °C and 26 °C. NH3 concentrations in the animal-occupied zone were dependent on ST insofar as ST controlled the operation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…The daily evolution of NH 3 concentration showed a sinusoidal response for weaned piglets [60], which is in agreement with the results for odor and pollutant emission from finishing pigs [51]. NH 3 concentration in the animal-occupied zone varies with the temperature setpoint defined for the climate control system.…”
Section: Concentration Of Gasessupporting
confidence: 88%
See 2 more Smart Citations
“…The daily evolution of NH 3 concentration showed a sinusoidal response for weaned piglets [60], which is in agreement with the results for odor and pollutant emission from finishing pigs [51]. NH 3 concentration in the animal-occupied zone varies with the temperature setpoint defined for the climate control system.…”
Section: Concentration Of Gasessupporting
confidence: 88%
“…At night, when air temperature is lower, the ventilation rate decreases, which causes an increase in NH 3 concentration. [50,52,60,61].…”
Section: Concentration Of Gasesmentioning
confidence: 99%
See 1 more Smart Citation
“…When air characterized by a high speed passes over the free surface of the manure, the emissions increase. Rodriguez et al [39] found an inverse behavior between NH 3 concentration and relative humidity, and a direct relation between NH 3 concentration and indoor air temperature in weaning rooms, results that are similar to the ones of Banhazi [35].…”
Section: Climate Control and Air Emissionssupporting
confidence: 54%
“…The most important factors affecting this process are the urinary urea concentration, pH and slurry temperature (Colina et al, 2000). NH3 concentrations in swine buildings show large variations and are related to a number of factors, including animal age, activity and density, outdoor temperature, ventilation control (Rodriguez, 2020). Ammonia emissions are obviously influenced by season with typically higher emission rates during summer time (about 7.0 g NH3/pig/day) and lower emission during winter time (about 3.0 NH3/pig/day).…”
Section: )mentioning
confidence: 99%